Molecular detection of aminoglycosides modifying enzymes and its relationship to drug resistance in Pseudomonas aeruginosa - Sara Al-janaby; Mayada Shehan (مجلة جامعة الانبار للعلوم الصرفة, 2023)
Pseudomonas aeruginosa is an opportunistic pathogen that causes a variety of infections throughout the world, including bacteremia in immunocompromised patients, wound and soft tissue infections, hospital-acquired pneumonia, respiratory infections, and urinary tract infections. It is also the primary cause of life-threatening infections in burn patients. A total of 120 specimens were collected from Al-Anbar Province hospitals, they were obtained from a wound (65.85%), burns (52.63), UTI (33.33%),and sputum (48.27%). Out of these specimens, 65 isolates were bacteriologically identified as P.aeruginosa depending on cultural and microscopical properties, automated (VITEK-2 system), and molecular identification based on 16SrRNA gene, which is an essential gene expressed isolates in all P.aeruginosa. The antimicrobial susceptibility test was done by using the disc diffusion method of aminoglycoside antimicrobials. The results appeared the highest resistance to Gentamycin (81.53%), Amikacin (73.84%), then Tobramycin (66.15%), and Netilmicin (33.84%). Molecular analysis of aminoglycosides modifying enzymes genes showed that the percentage of the AAC(6 ′ )-Ib gene was highest 16/20 (85%), then 8/20 (40%), 2/20 (10%) for ANT (3 ″ )-Ia , APH(3 ′ )-IIb, respectively.